A new species of Begonia section Casparya from the Colombian Eastern Cordillera and a key to the Colombian Casparya - Jara-Muñoz, Orlando A.; Richardson, James E.; Madriñan, Santiago (Phytotaxa, 2017)
A new species, Begonia solaniflora Jara is described from Colombia. This species belongs to section Casparya as evident by the fruit type, but is also easily distinguished from other Casparya species by the undivided or rarely bifid styles, the stamens erect with the anthers connivent and the nearly symmetrical leaves. We provide illustrations, photographs, a distribution map of the species and after an assessment of its conservation status we propose to place it in the Critically Endangered (CR) category.